Comparative investigation of the structural characteristics of tobacco stalk lignin during the DES and alkaline deconstruction toward sustainable materials - Wang, Na; Wang, Bo; Si, Hui; Hu, Suxia; Chen, Lin; Liao, Yu; Wang, Lei; Zhang, Yifan; Jiang, Jungang (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin polymer as a natural aromatic macromolecule presents significant prospects in producing functional and sustainable materials, and achieving a comprehensive characterization will facilitate their target valorization. In the present study, deep eutectic solvent (DES) and alkaline delignification were adopted to deconstruct tobacco stalk before and after hydrothermal pretreatment, obtaining diverse lignin fractions with fascinating characteristics. DES lignin exhibited a higher yield and homogenous molecular structure than MWL. A severe cleavage of the inter-unit linkages in lignin was also observed. This result mostly originated from the efficient delignification of the DES deconstruction system adopted. Moreover, all the recovered lignin fractions exhibited good micro-nanoparticle size that can enhance the valorization of lignin in nanomaterial production, in which the hydrothermal-assisted DES deconstruction promoted the formation of the smaller lignin nanoparticle size. Next, all the recovered lignin presented an excellent UV absorption and structure-related absorption performance or thermal properties. Overall, this work provides an important foundation for further exploiting DES/alkaline delignification lignin that can be applied as an ideal feedstock for producing sustainable functional or micro/nanomaterials.